Desafíos y barreras en el manejo del dolor al final de la vida desde la perspectiva de enfermería - Pogo Requenes, Joselyne Priscila (2025)
Introduction: The work of pain management performed by health personnel in a critical area which is fundamental, and it is here where most palliative care is provided to ensure relief. In addition, the role in the nursing area includes providing the necessary support, whether emotional or in accompanying family members. Objective: The aim of this literature review was to identify the challenges and barriers to pain management at the end of life from a nursing perspective. Methodology: A mostly qualitative approach was used, which is represented by information from 25 articles from different databases such as Elsevier, Recimundo, Springer, Science Direct, etc, from the year 2020 to 2024, where those articles that can provide relevant information are considered. According to the objective, it is of the applied type; in which existing theories and knowledge are used to identify various roles. According to its scope, it is descriptive; the objective is to describe the nursing role in pain management. It is also cross - sectional, non - experimental in nature. Results: It is evidenced how important is the role of health personnel in the care of those critical palliative patients; challenges and deficiencies should be leveraged as much as possible, leading to an improvement in the quality of care. Conclusions: it was possible to identify the challenges and barriers in the management of pain at the end of life. It also involves various aspects such as the administration of analgesics, when dealing with emotional aspects.